Peran Komitmen Organisasi Memediasi Kompetensi dan Skeptisisme Profesional Terhadap Efektivitas Audit Investigasi - Yana Mustika; Harti Budi Yanti (CV. Publikasi Indonesia, 2022)
his study was conducted to examine and explain the effect of professional competence and skepticism on the effectiveness of investigative audits with organizational commitment as a mediating variable. The population in this study is the investigative auditor at the Auditor Utama of Badan Pemeriksa Keuangan Republik Indonesia (BPK-RI). The sample in this study amounted to 59 investigative auditors. Collecting data using a questionnaire with a Likert scale. Data analysis used the Partial Least Square (PLS) method with an explanatory approach and WarpPLS 7.0 as an analytical tool. The results of this study indicate that professional competence and skepticism have a positive effect on the effectiveness of investigative audits. Meanwhile, organizational commitment can mediate the effect of competence and skepticism on the effectiveness of investigative audits.